Sodium chloride on dry biomass and macronutrient cations absorption in cempasúchil (Tagetes erecta Linn.) - Trejo-Téllez, Libia Iris; Peralta Sánchez, María Guadalupe; Gómez-Merino, Fernando Carlos; Rodríguez- Mendoza, María de las Nieves; Serrato-Cruz, Miguel Ángel; Arévalo-Becerril, Ángel Enrique (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this research was to evaluate the addition of two concentrations of NaCl (10 and 47 mM) to the nutrient solution on biomass production, concentration and accumulation of K +, Ca2+, Mg2+ and Na+ in f lowers, leaves, stems and roots of cempasúchil (Tagetes erecta Linn.) cv. Inca during the f lowering phase. The plants were established in the greenhouse in plastic pots using as substrate a mixture of tezontle: perlite (60:40, v: v). Nutrient solutions with both concentrations of NaCl were supplied by a dripping irrigation system. The addition of 47 mM of NaCl reduced the dry biomass of flowers and stems, compared with the 10 mM treatment, these reductions were 42.6 and 16.5%, respectively. The concentrations of K+, Ca2+ and Mg2+ in leaves were not affected by the NaCl concentration in the nutrient solution, although the accumulation of K+, Ca2+ and Mg2+ in the f lowers, leaves and stems was significantly reduced with am increased NaCl concentration in the solution. The concentration and accumulation of Na+ in all organs had a positive relationship with the concentration of NaCl and the ability of Na+ exclusion from leaves it ́s easily observed, introducing these lower values of concentration and accumulation, compared with other organs. While it had low concentrations of Na+ in the flowers, compared with other organs, the accumulation value of this elements in the f lowers were just under the root.
Keywords: accumulation; concentration of cations; calcium; potassium; magnesium